Linear Control Applied to a Non-Isolated Bidirectional Dc-Dc Converter with Interleave Technique Powered by Variable Sources - Rojas-Lobos, F; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2019)
In this article, a linear control strategy is presented applied to a Synchronous Buck converter, which allows N sub-converters to operate in parallel, operating in Interleave mode, balancing the currents in each of the sub-converters and maintaining their dynamic response invariant over a wide range of operation, even when their DC links vary as it would be in a system with electric batteries. Simulation results validating this behavior, using variable DC sources are presented and discussed in this article. © 2019 IEEE.